PERFORMANCE OF THE BIOMEDICAL IN AESTHETIC BIOMEDICINE - Caruliny Rosa dos Santos, Geovana; Gomes Guimarães, Herika; Rafaela de Oliveira Moreira , Lana; Candida Silva Pereira Farias, Mayla; Alves Moreira, Nayara; Júlia Andrade Batista Filha, Ana; Henrique da Silva, Bruno; Silva Gomes, Fabiana; Adriel Feitosa da Silva, Carlos; Lucena Nunes , Poliana (CIPEEX, 2025)
Introduction: The performance of biomedical professionals in aesthetic biomedicine was formally recognized by Biomedicine in May 2019, through Resolution No. 307. This area is constantly evolving and is considered a promising field within health and wellness. Driven by the search for standards of beauty and self-esteem, this specialty allows the biomedical professional to work in the development and application of various treatments for facial and body aesthetic dysfunctions and those related to aging. Objective: To promote a bibliographic study on the performance of biomedical professionals in aesthetic biomedicine, highlighting their responsibilities and importance during facial, body and hair aesthetic procedures. Methodology: A narrative literature search was carried out between June and August 2025, using the following keywords: Aesthetic Biomedicine (AND) Self-Esteem (OR) Aesthetic Procedures. Searches were carried out in the Virtual Health Library database, including complete scientific articles published in Portuguese and English, which addressed professional performance in aesthetics. The following keywords were used: aesthetic procedures (and) face (or) body (or) capillary (and) trends. Results: The research showed that in addition to the physical aspects, the aesthetic treatments promoted by biomedical professionals positively impact on the self-esteem, self-image and quality of life of individuals, helping to minimize discomfort and complexes with appearance. Among the procedures that the biomedical esthete is qualified to perform are electrotherapy, aesthetic ultrasound (sonophoresis), radiofrequency, laser therapy, intense pulsed light and LED, chemical and mechanical peels, carboxytherapy, intradermotherapy, semi-permanent fillers and application of botulinum toxin. Conclusion: The Federal Council and the Regional Councils of Biomedicine strictly regulate and supervise the performance of the biomedical aesthete, establishing limits and essential conducts for patient safety.